2004
DOI: 10.1023/b:bebm.0000028124.90768.50
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Diquertin-Mediated Regulation of Neutrophil Function in Patients with Non-Insulin-Dependent Diabetes Mellitus

Abstract: We studied the effects of dihydroquercetin (3.3.4.5.7-pentahydroxyflavanone, a new Russian patented preparation) on functional activity of polymorphonuclear neutrophils from patients with non-insulin-dependent diabetes mellitus. Flavonoids (quercetin and its derivative dihydroquercetin) dose-dependently suppressed generation of anion radicals and hypochlorous acid and production of malonic dialdehyde during oxidation of neutrophil membranes. Dihydroquercetin decreased activities of protein kinase C and myelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As a ubiquitous constituent of foods and herbs, taxifolin is consumed regularly in the human diet and exerts a wide range of biochemical and pharmacological effects; these include antioxidant [9,10], antitumor [11] and anti-inflammatory effects [12], the prevention of Alzheimer’s disease [13], antidiabetic [14,15], antiviral [16], antimicrobial [17], hepatoprotective [18], cardioprotective [15,19], neuroprotective [20] and immunoregulatory effects [21], and xanthine oxidase inhibition [22]. Additionally, experimental data indicate that taxifolin use is safe and nontoxic [2,23].…”
Section: Introductionmentioning
confidence: 99%
“…As a ubiquitous constituent of foods and herbs, taxifolin is consumed regularly in the human diet and exerts a wide range of biochemical and pharmacological effects; these include antioxidant [9,10], antitumor [11] and anti-inflammatory effects [12], the prevention of Alzheimer’s disease [13], antidiabetic [14,15], antiviral [16], antimicrobial [17], hepatoprotective [18], cardioprotective [15,19], neuroprotective [20] and immunoregulatory effects [21], and xanthine oxidase inhibition [22]. Additionally, experimental data indicate that taxifolin use is safe and nontoxic [2,23].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has a potential role in the pathogenesis of diabetes. Fedosova et al found that quercetin could reduce the oxidative function of polymorphonuclear neutrophils (PMN) in patients with non-insulin-dependent diabetes mellitus (NIDDM) [ 76 ]. Quercetin exerted its antioxidant effects by directly inhibiting the production of lipid peroxides, such as malondialdehyde (MDA) and thiobarbituric acid-reactive substances (TBARS), and indirectly promoting the production of endogenous antioxidants, such as antioxidant enzymes glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT), in STZ-induced diabetic rats and db/db mice [ 55 , 75 , 77 – 85 ].…”
Section: Pharmacological Effects and Molecular Mechanisms Of Quercetin Against Three Metabolic Diseasesmentioning
confidence: 99%
“…With highly oxidizable flavonoids (e.g., quercetin), autoxidation can take place and has been investigated in physiological conditions (pH 7.5 aqueous buffers) 25,26. The investigations also showed that the secondary products of flavonoid oxidation may have deleterious consequences in biological systems 27–35.…”
Section: Introductionmentioning
confidence: 98%